2011
DOI: 10.1121/1.3651822
|View full text |Cite
|
Sign up to set email alerts
|

Vibration responses of the organ of Corti and the tectorial membrane to electrical stimulation

Abstract: Coupling of somatic electromechanical force from the outer hair cells (OHCs) into the organ of Corti is investigated by measuring transverse vibration patterns of the organ of Cori and tectorial membrane (TM) in response to intracochlear electrical stimulation. Measurement places at the organ of Corti extend from the inner sulcus cells to Hensen's cells and at the lower (and upper) surface of the TM from the inner sulcus to the OHC region. These locations are in the neighborhood of where electromechanical forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 102 publications
10
52
1
Order By: Relevance
“…Then, the BM motion and the shearing motion between the TM and RL are calculated when the slice is driven either acoustically or electrically, and these results are also compared with previous experimental observations [5,[9][10][11]. The fully active response of the BM to acoustic excitation is then predicted, assuming small displacements, using a linear superposition of the calculated responses, with feedback provided by an appropriately defined gain function for the OHCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the BM motion and the shearing motion between the TM and RL are calculated when the slice is driven either acoustically or electrically, and these results are also compared with previous experimental observations [5,[9][10][11]. The fully active response of the BM to acoustic excitation is then predicted, assuming small displacements, using a linear superposition of the calculated responses, with feedback provided by an appropriately defined gain function for the OHCs.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive measurements of the internal motion within the organ of Corti are difficult, particularly in vivo in the fully active cochlea [4], but measurements with acoustic excitation of the partly active cochlea [5][6][7][8] are possible. Experimental observations of internal motion of the organ of Corti using in vivo or in vitro preparations have been reported, for acoustic excitation, by Nilsen & Russell [5], and Lee et al [9], by Nowotny & Gummer [9,10] for electrical excitation, by Chan & Hudspeth [11] for both excitation modes and by Fridberger et al [6] for static pressure loading. Even though there is still some debate about the role of the hair bundle dynamics [12 -18], it is widely believed that it is mainly the somatic motility of the OHCs that provides the power to drive the amplification of the vibration within the mammalian organ of Corti [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned, however, that more recent models of OHCbased amplification do not have lags required of older models (59). Based on new concepts, it is not OHC action on the basilar membrane, but instead on the fluid micromechanics of the subtectorial membrane space that affords amplification (60,61). Although our data are in harmony with the phase-lag requiring models, it remains to be seen how our predicted phase characteristics of the OHC motor impact on newer models, and whether the throttling kinetics of prestin's intermediary gateway can influence amplification.…”
Section: Models Of Prestinmentioning
confidence: 99%
“…Due to its attachment with the hair bundles of outer hair cells, this radial movement modulates conductance of mechanoelectrical transduction channels and converts acoustical information into electrical signals [1,20]. The tectorial membrane may also function as a resonator that amplifies the input to the hair bundle [4,10,11,20]. Recent studies using genetically modified mice demonstrated that the tectorial membrane enabled the motion of the basilar membrane to optimally stimulate the sensory inner hair cells at the best frequency [18].…”
Section: Introductionmentioning
confidence: 99%
“…As sensors and effectors, outer hair cells not only detect, but also generate sounds. The mechanical coupling between the tectorial membrane and hair bundles of outer hair cells is also critical for transmitting cellular forces back to the basilar membrane for enhancing hearing sensitivity [11] and for generating otoacoustic emissions.…”
Section: Introductionmentioning
confidence: 99%